2012
DOI: 10.1007/s12035-012-8365-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Grey Matter Loss Determined by MRI Is Primarily Due to Loss of Dendrites and Their Synapses

Abstract: Stress, unaccompanied by signs of post-traumatic stress disorder, is known to decrease grey matter volume (GMV) in the anterior cingulate cortex (ACC) and hippocampus but not the amygdala in humans. We sought to determine if this was the case in stressed mice using high-resolution magnetic resonance imaging (MRI) and to identify the cellular constituents of the grey matter that quantitatively give rise to such changes. Stressed mice showed grey matter losses of 10 and 15 % in the ACC and hippocampus, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 110 publications
12
124
1
Order By: Relevance
“…The AC is highly vulnerable to stress-related changes in noradrenergic activity (Hermans et al, 2011) and, like the hippocampus, shows grey matter loss following a variety of stressful conditions, including childhood adversity, in individuals with or without a PTSD diagnosis (Ansell et al, 2012;Dannlowski et al, 2012;Karl et al, 2006). Although the current study is unable to conclusively inform about the direction of causality in the observed relationship between AC volume and psychosocial deprivation/abuse, a number of studies have clearly shown AC grey matter loss in people experiencing stressful life events and cumulative life adversities with no psychiatric diagnosis (Ansell et al, 2012;Ganzel et al, 2008;Papagni et al, 2011), as well as in animals following exposure to stress (Cerqueira et al, 2005;Kassem et al, 2013).…”
Section: Discussionmentioning
confidence: 69%
“…The AC is highly vulnerable to stress-related changes in noradrenergic activity (Hermans et al, 2011) and, like the hippocampus, shows grey matter loss following a variety of stressful conditions, including childhood adversity, in individuals with or without a PTSD diagnosis (Ansell et al, 2012;Dannlowski et al, 2012;Karl et al, 2006). Although the current study is unable to conclusively inform about the direction of causality in the observed relationship between AC volume and psychosocial deprivation/abuse, a number of studies have clearly shown AC grey matter loss in people experiencing stressful life events and cumulative life adversities with no psychiatric diagnosis (Ansell et al, 2012;Ganzel et al, 2008;Papagni et al, 2011), as well as in animals following exposure to stress (Cerqueira et al, 2005;Kassem et al, 2013).…”
Section: Discussionmentioning
confidence: 69%
“…Stress exposure has been shown to result in spine loss in hippocampus CA3 cells [69, 89, 92, 98, 106, 107], although increased or no change in spine density has also been reported [72, 108]. Stress-induced spine loss has been shown in CA1 (and CA3) along with impaired synaptic transmission and depressive behaviors [49, 92]. Decreased spine densities in CA1 neurons has been associated with depression-like behaviors in a light-induced depression model, in the absence of spine changes in CA3 or dendritic changes in CA3 or CA1 [4].…”
Section: Chronic Stress Alters the Number And Function Of Spine Synapsesmentioning
confidence: 99%
“…It has been suggested that abnormal regional brain volume in OCD might result from a combination of abnormal neurodevelopmental processes and additional altered aging-related trajectories due to several factors operating on multiple levels-for example, genetic variations influencing neuronal pruning and aging processes, activity-dependent neuronal plasticity associated with chronic symptoms or compensatory processes, and neurochemical effects of pharmacological treatment or stress (30,31). Patients showed relative preservation of the putamen, nucleus accumbens, and inferior and orbitofrontal cortex during aging, which was in contrast to the loss associated with healthy aging (18).…”
Section: Altered Brain Volume Changes In Ocd During Agingmentioning
confidence: 99%
“…The fusiform, parahippocampal, and inferior temporal cortices are involved in higher-level visual processing, visual emotional perception (39), and emotional memory formation (40). Greater volume loss in these regions may thus be related to chronic stress and the exaggerated emotional responsiveness seen in OCD (1,31).…”
Section: Altered Brain Volume Changes In Ocd During Agingmentioning
confidence: 99%